E. T. A. Hoffmann e Jacques Callot: a ficção da imagem - Volobuef, Karin [UNESP] (My University, 2011)
Hoffmann wrote several fairy tales, including "Princess Brambilla" (1821), which has an remarkable pictorial component: when it was published, the text went along with eight illustrations by Carl Friedrich Thiele, which were derived from original prints made by the Frenchman Jacques Callot. While Callot images portray the Italian theater of the Commedia dell'Arte, Thiele's works follow the plot of the narrative, representing the characters of Hoffmann, who disguise themselves because of the carnival that is taking place in Rome. The costumes and masks worn by the characters however do not ensure them full secrecy. Instead of a complete undercover, they lead to double meanings and double identities so that narrative levels and artistic references overlap and create an effect similar to a set of a polyphonic orchestra (which is a metaphor implied in the very subtitle, where the narrative is called a Capriccio).

E. T. A. Hoffmann escreveu vários contos de fadas, entre os quais "Princesa Brambilla" (1821), que se destaca devido a sua dimensão pictórica: a narrativa foi publicada juntamente com oito ilustrações de Carl Friedrich Thiele, as quais foram elaboradas a partir de gravuras originalmente feitas pelo francês Jacques Callot. Enquanto as imagens de Callot retratam figuras do teatro italiano da Commedia dell'Arte, as de Thiele acompanham o enredo da narrativa, representando os personagens de Hoffmann, que se fantasiam para mergulhar no carnaval de Roma. As fantasias e máscaras usadas pelos personagens, porém, não garantem simplesmente o anonimato daqueles que as vestem para se divertir incógnitos; mais do que isso, elas criam duplicidade de sentidos e de identidade, e fazem com que planos narrativos e referências artísticas se sobreponham, criando um efeito semelhante ao do conjunto polifônico de uma orquestra (metáfora inclusive insinuada no próprio subtítulo, em que a narrativa é denominada de Capriccio).
Keywords: E. T. A. Hoffmann; Princess Brambilla; Polyphony; Jacques Callot; Commedia dell'Arte; E. T. A. Hoffmann; Princesa Brambilla; Polifonia; Jacques Callot; Commedia dell'Arte